Identification des matériaux et étude du bâti : l’exemple du Clos du Cotentin - Julien Deshayes (In Situ, 2012)
Based on the vernacular architecture of the Cotentin peninsula, this article sets out to show how the identification of construction materials, placed in a historical context, can offer a particularly useful tool for analysing buildings, notably for their chronology. The identification of the principle stone quarries and their zones of commercial influence gives information on the evolution of architectural proportions and permits the development of coherent typologies. The acquisition of such analytical criteria is difficult to generalise beyond strictly limited regions and are necessarily linked with in-depth familiarity with the territory concerned. The example that the Clos du Cotentin offers for the identification of building materials and the study of buildings may be seen as a manifesto in favour of a detailed topographical approach, capable of placing rural architecture in the framework of its historical evolution.